SAFe 4.5 distilled : applying the Scaled Agile Framework for Lean enterprises - Knaster, Richard; Leffingwell, Dean (Addison-Wesley, 2019)
SAFe®: The World's Leading Framework for Enterprise Agility "Philips is continuously driving to develop high-quality software in a predictable, fast, and Agile way. SAFe addresses this primary goal, and offers these further benefits: reduced time-to-market, improved quality, stronger alignment across geographically distributed multi-disciplinary teams, and collaboration across teams to deliver meaningful value to customers with reduced cycle time."--Sundaresan Jagadeesan, SW CoE Program Director, Philips To succeed in today's adapt-or-die marketplace, businesses must be able to rapidly change the way they create and deliver value to their customers. Hundreds of the world's most successful companies-including Intel, Capital One, AstraZeneca, Cisco, and Philips-have turned to the Scaled Agile Framework® (SAFe®) to achieve agility at scale and maintain a competitive edge. SAFe® 4.5 Distilled: Applying the Scaled Agile Framework® for Lean Enterprises explains how adopting SAFe can quickly improve time to market and increase productivity, quality, and employee engagement. In this book, you will Understand the business case for SAFe: its benefits, the problems it solves, and how to apply it Get an overview of SAFe across all parts of the business: team, program, value stream, and portfolio Learn why SAFe works: the power of SAFe's Lean-Agile mindset, values, and principles Discover how systems thinking, Agile development, and Lean product development form the underlying basis for SAFe Learn how to become a Lean-Agile leader and effectively drive an enterprise-wide transformation Register your book for convenient access to downloads, updates, and/or corrections as they become available. See inside book for details